PEMBUATAN DAN PELATIHAN SISTEM INFORMASI SEBAGAI UPAYA PENINGKATAN KINERJA DC MALL BATAM - Gormantara, Alfredo; Carolus, Ridnaldy Yunior; Sumarta, Sean Coonery (LPPM Universitas Nusa Mandiri, 2024)
Digital transformation in Industry 5.0 has become a driving force in moving companies to improve the quality of services provided to customers and ease of work. The company's needs in carrying out strategic work and policies cannot be separated from the use of systems to help manage company data. DC Mall rents out its locations to parties such as shopping centers, supermarkets, exhibition corridors, restaurants and electronics stores. One of the routine tasks in managing DC Mall is paying utilities and rent for each unit. Payments are made to the mall management every month. Efforts to develop an information system that can cover all parts of mall management, including finance, customer service, marketing and others. The aim of this activity is to implement an information system at DC Mall that is beneficial for employee and company performance. The new system is designed to cover the weaknesses of the previous system. This service activity, which includes observation, data collection, design, implementation and evaluation, was carried out for approximately three months, starting from November 10 to January 19 2024. Each member is responsible for making observations, surveying locations, collecting data, helping create information systems and training employees, and compiling service reports. Based on the results of the service, it can be concluded that the creation of the new DC Mall information system has been successful based on feedback from employees in operating and carrying out their duties.